Colloid science : principles, methods and applications - Cosgrove, T. (Wiley, 2010)
Colloidal systems are important across a range of industries, such as the food, pharmaceutical, agrochemical, cosmetics, polymer, paint and oil industries, and form the basis of a wide range of products (eg cosmetics & toiletries, processed foodstuffs and photographic film). A detailed understanding of their formation, control and application is required in those industries, yet many new graduate or postgraduate chemists or chemical engineers have little or no direct experience of colloids. Based on lectures given at the highly successful Bristol Colloid Centre Spring School, Colloid Science.